The impact of domestic political challenges towards the accession of Bulgaria to the European Union in January 2007 - Tassev, Valentin (My University, 2008)
The following research report will look at a series of domestic factors that posed a threat to Bulgaria’s integration into the European Union in January 2007. In this light, this research report will evaluate the efforts that Bulgarian political leaders have taken to meet those existing domestic political challenges and thus assess Bulgaria’s progress towards meeting the political and economic criteria towards EU membership. This research study will be explained by the theoretical tradition of the multi-level governance approach, which assumes the involvement of supranational, national and sub-national actors in the processes of European integration.
Keywords: EU; Bulgaria; European Union; integration; enlargement; EU membership criteria; political challenges